ANALYSIS OF INFILTRATION WELLS AS PRO-CONSERVATION DRAINAGE (Case Study of Kalongan, Maguwoharjo, Depok, Sleman, Yogyakarta) - Lilik Hendro Widaryanto (Journal of Green Science and Technology, 2022)
Indonesia has two seasons, namely the dry season and the rainy season where the rainfall in the two seasons has a very large difference. Rainfall in the rainy season will be a source of groundwater reserves, because in the dry season there tends to be no rain. Efforts to increase groundwater reserves are carried out, among others, to use environmentally friendly drainage, namely by using infiltration wells and water will be infiltrated so as to reduce runoff.This research will begin by mapping the land covered by buildings in Kalongan and then calculating the area of land covered by the buildings. Rainfall data used is data at the Maguwoharjo rain station which is close to Kalongan with a span of 10 years. The number of infiltration wells currently available is 8 and by analyzing the needs of infiltration wells it will be known how many infiltration wells are needed so that as much water can be infiltrated to reduce runoff and increase groundwater reserves.The results of the frequency analysis for rainfall with a maximum return period of 5 years as a basis for planning infiltration wells. This large runoff during the rainy season can be reduced by having sufficient infiltration wells, so that rainwater entering the infiltration well will become a source of groundwater reserves. The total requirement for infiltration wells is 464 pieces with a diameter of 80 cm and a depth of 3 m. There are 8 infiltration wells so it is necessary to make 456 infiltration wells to reduce runoff.Keyword: groundwater, infiltration, runoff